Low birth weight of Vietnamese infants is related to their mother’s dioxin and glucocorticoid levels - Van Tung, Dao; Kido, Teruhiko; Honma, Seijiro; Manh, Ho Dung; Nhu, Dang Duc; Okamoto, Rie; Maruzeni, Shoko; Nishijo, Muneko; Nakagawa, Hideaki; Ngoc, Pham Thien; Van Toan, Ngo; Hung, Nguyen Ngoc; et al. (Environmental science and pollution research international, 2016)
We aimed to determine the relationship between dioxin congeners in maternal breast milk and maternal glucocorticoid levels with newborn birth weight after nearly 45 years of use of herbicides in the Vietnam War. The study subjects comprised 58 mother–infant pairs in a region with high dioxin levels in the soil (hotspot) and 62 pairs from a control region. Dioxin levels in maternal breast milk were measured by HRGC-HRMS. Salivary glucocorticoid levels were determined by LC-MS/MS. Dioxin congener levels in mothers from the hotspot were found to be two to fivefold higher than those in mothers from the control region. Birth weight was inversely correlated with 2,3,7,8-TeCDD and 2,3,4,7,8-PeCDF congener levels. The rate of newborns whose birth weight was less than 2500 g was threefold higher in the hotspot (12 %) than in the control region (4 %). Salivary glucocorticoid levels in mothers with low birth weight infants were significantly higher than those in the normal birth weight group. Low birth weight of Vietnamese newborns in a hotspot for dioxin levels is related to some dioxin congener levels and high glucocorticoid levels in mothers. This finding in mother–infant pairs suggests that excess maternal glucocorticoid levels are related to dioxin burden and they result in low birth weight.